Analysis of the impact of energy consumption on regional agricultural economic growth based on panel data - Jiang, Tianlong; Chen, Zhongsheng (Frontiers in Ecology and Evolution, 2023)
Energy is an important resource for human survival and development. China has now become the world's second largest energy consumer, and its energy consumption growth rate ranks first. However, if the current consumption pattern continues to develop, With China's rapid economic growth, China's economic development would inevitably be limited by energy. In addition, although China's economic growth rate is very fast, the change of energy structure has also brought a negative impact on people's lives. Therefore, the paper studied the relationship between energy consumption and economic development between different regions by focusing on three regions. The results showed that there was no one-way or two-way causality in Class I regions with high economic development and high energy consumption whether in the short term or in the long run; In the Class II areas with high economic development and low consumption, there was a two-way causal relationship between energy consumption and economic development in the short term. In the long run, economic growth was a one-way causal relationship; in the Class III regions with slow economic growth and low energy consumption, only long-term energy consumption was a single causal relationship of economic development below the 10% significant level. The long-term and short-term causal relationship between energy consumption and economic development varied significantly from region to region. Therefore, in order to coordinate regional economic development and shorten the regional gap, it was necessary to formulate appropriate regional energy consumption policies and strategies.